2022
DOI: 10.1002/acr.24501
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Minimal and Meaningful Change in a Patient‐Reported Outcomes Measurement Information System for Rheumatoid Arthritis: Use of Multiple Methods and Perspectives

Abstract: Objective Rheumatoid arthritis (RA) is chronic, painful, disabling condition resulting in significant impairments in physical, emotional, and social health. Our objective was to use different methods and perspectives to evaluate the responsiveness of Patient‐Reported Outcomes Measurement Information System (PROMIS) short forms (SFs) and to identify minimal and meaningful score changes. Methods Adults with RA who were enrolled in a multisite prospective observational cohort completed PROMIS physical function, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…21 Moreover, using adults with RA enrolled in a multisite observation cohort, a recent study also found a 1-3 points change in PROMIS scores for several PRO measures when patients felt a little better or a little worse. 22 In addition, the mean and IQRs of the PROMIS t-score for fatigue and pain interference scores in our study cohort do not indicate an issue with floor or ceiling effects.…”
Section: Discussionmentioning
confidence: 46%
“…21 Moreover, using adults with RA enrolled in a multisite observation cohort, a recent study also found a 1-3 points change in PROMIS scores for several PRO measures when patients felt a little better or a little worse. 22 In addition, the mean and IQRs of the PROMIS t-score for fatigue and pain interference scores in our study cohort do not indicate an issue with floor or ceiling effects.…”
Section: Discussionmentioning
confidence: 46%
“…However, it is noteworthy that reported minimally important differences vary across the different PROMIS domains and across different patient populations. For example, in patients with rheumatoid arthritis, changes as small as 1-2 points are associated with noticeable improvements in domains such as fatigue and pain interference [15,24,32], and meaningful change thresholds for these domains have been defined as 2-3 points [34]. Minimal important differences have been reported to be approximately 2 points for PROMIS domains of physical function, fatigue, pain interference, and social participation in patients with systemic lupus erythematosus [33] and to be approximately 2 points for physical function and pain interference in patients with knee osteoarthritis or other chronic musculoskeletal pain [19,25].…”
Section: Discussionmentioning
confidence: 99%
“…Modified cumulative distribution curves [23] were generated to show the proportions of patients achieving various levels of improvement in each PROMIS-29 domain T-score from ≥ 1 to ≥ 21 points at Week 24 by treatment group. Based on published studies estimating clinically meaningful changes and minimally important differences in PROMIS domain scores in patients with rheumatic and musculoskeletal disorders [15,[24][25][26][27], two prespecified thresholds (≥ 5and ≥ 3-point improvement) were used to define clinically meaningful changes in each domain T-score. At Week 24, achievement of point improvement thresholds was calculated for all patients who had not met treatment failure criteria; patients with missing data were considered non-responders.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Patient-Reported Outcomes Measurement Information System (PROMIS Ò ), developed by the National Institutes of Health [11,12], is a disease-agnostic set of health assessment instruments designed to efficiently evaluate and monitor HRQoL across numerous aspects of physical, emotional, and social health [11][12][13]. PROMIS can be used to assess the health status of individuals in the general population as well as in those with chronic conditions and has been validated in patients with RA [14,15]. PROMIS measures have greater precision than the 36-item Short-Form Health Survey [SF-36] and improved responsiveness to change when assessing physical function [16].…”
Section: Introductionmentioning
confidence: 99%